Unstented laparoscopic pyeloplasty in young children (1-5 years old): a comparison with a repair using double-J stent or transanastomotic externalized stent - Kočvara, Radim; Sedláček, Josef; Drlík, Marcel; Dítě, Zdeněk; Běláček, Jaromír; Fiala, Vojtěch (Journal of pediatric urology, 2014)
OBJECTIVE: To evaluate feasibility of unstented laparoscopic pyeloplasty in young children to prevent pyelonephritis and second anaesthesia. PATIENTS AND METHODS: During 2006-2013, 70 children (1-5 years old) underwent laparoscopic pyeloplasty for high grade hydronephrosis. Unstented repair was indicated in 34 children (GroupL1), double-J stent was placed in 21 patients (Group L2) and uretero-pyelostomy stent (Cook) in 15 patients (Group L3). Stenting was preferred in large thin-walled pelvis, thin ureter, kidney malrotation, and unfavourable course of crossing vessels. The outcome was compared with age-matched group of 52 children who had open surgery during 1996-2006 (Groups O1, O3). RESULTS: Operation times were significantly shorter in Groups L1 and L2 than in Group L3; the times were shorter in open repairs. Three patients with crossing vessels from Group L1 had urine leakage and one had obstruction (11.4%). In Group L2, one patient had obstruction, one incorrect placement of the stent, and one girl had serious pyelonephritis (14.3%). In Group L3, displacement of uretero-pyelostomy occurred in one patient (6.7%). There is no statistical difference between laparoscopic groups and between laparoscopic and open groups. CONCLUSION: Unstented laparoscopic pyeloplasty is a safe procedure in selected young children with favourable anatomical conditions preventing additional anaesthesia and stent-related complications.
Keywords: laparoskopie; Infant; Hydronephrosis; hydronefróza; urologické chirurgické výkony; Length of Stay; Urologic Surgical Procedures; předškolní dítě; Humans; Laparoscopic pyeloplasty in children; Kidney Pelvis; Pyelonephritis; pyelonefritida; ledvinná pánvička; stenty; obstrukce močovodu; Double-J stent in children; Ureteropelvic junction obstruction; mužské pohlaví; Unstented laparoscopic pyeloplasty; Laparoscopy; Child, Preschool; Ureteral Obstruction; Prosthesis Design; Stents; délka pobytu; ženské pohlaví; Paediatric pyeloplasty; lidé; dítě; Child; protézy - design; Male; kojenec; Female